Islamic Economics in Scholarly Publications (2000–2025): Influential Topics, Leading Sources, and Intellectual Linkages - Judijanto, Loso (Westscience Press, 2026)
In order to understand the existing literature on Islamic economics, we conducted a bibliometric analysis of publications dedicated to the topic and published between 2000 and 2025 that were included in the Scopus database. With the help of VOSviewer, we performed an analysis of co-authorship, citation patterns, and keywords co-occurrences in order to reveal influential topics, important sources, and knowledge networks among researchers of Islamic economics. As a result of the analysis, we have determined that the research on Islamic economics has been based on a rather small set of central scholars, organizations, and even countries, which, however, have made a considerable contribution to building the knowledge base in the area. The results of our citation analysis suggest that the intellectual basis of the studied literature is based on a combination of ethical, normative, and socio-political discussions, which gradually shifted towards more applied and interdisciplinary studies, specifically in such spheres as Islamic finance and economic development. According to the results of keyword analysis, we can claim that the dominant theme of Islamic economics research papers is Islamic finance (Islamic banking), whereas the other emerging areas include sustainable development, information management, and financial innovation. The study contributes by providing a comprehensive mapping of Islamic economics research and offers insights into future directions, emphasizing the need for stronger global collaboration and broader thematic expansion to enhance the field’s relevance in addressing modern economic challenges.